Lymphatic fluctuation in the parenchymal remodeling stage of acute interstitial pneumonia, organizing pneumonia, nonspecific interstitial pneumonia and idiopathic pulmonary fibrosis - E.R. Parra; C.A.L. Araujo; J.G. Lombardi; A.M. Ab’Saber; C.R.R. Carvalho; R.A. Kairalla; V.L. Capelozzi (Brazilian Journal of Medical and Biological Research, 2012)
Because the superficial lymphatics in the lungs are distributed in the subpleural, interlobular and peribroncovascular interstitium, lymphatic impairment may occur in the lungs of patients with idiopathic interstitial pneumonias (IIPs) and increase their severity. We investigated the distribution of lymphatics in different remodeling stages of IIPs by immunohistochemistry using the D2-40 antibody. Pulmonary tissue was obtained from 69 patients with acute interstitial pneumonia/diffuse alveolar damage (AIP/DAD, N = 24), cryptogenic organizing pneumonia/organizing pneumonia (COP/OP, N = 6), nonspecific interstitial pneumonia (NSIP/NSIP, N = 20), and idiopathic pulmonary fibrosis/usual interstitial pneumonia (IPF/UIP, N = 19). D2-40+ lymphatic in the lesions was quantitatively determined and associated with remodeling stage score. We observed an increase in the D2-40+ percent from DAD (6.66 ± 1.11) to UIP (23.45 ± 5.24, P = 0.008) with the advanced process of remodeling stage of the lesions. Kaplan-Meier survival curves showed a better survival for patients with higher lymphatic D2-40+ expression than 9.3%. Lymphatic impairment occurs in the lungs of IIPs and its severity increases according to remodeling stage. The results suggest that disruption of the superficial lymphatics may impair alveolar clearance, delay organ repair and cause severe disease progress mainly in patients with AIP/DAD. Therefore, lymphatic distribution may serve as a surrogate marker for the identification of patients at greatest risk for death due to IIPs.